Pemanfaatan FMA Dan Tanaman Inang Atsiri Untuk Meningkatkan Pertumbuhan Bibit Cendana (Santalum album. L.) - Magdalena Sunarty Pareira; Yakobus Pffeferius Edvent Saba Agu (Savana Cendana, 2021)
Sandalwood (Santalum album L.) is one of the native trees of Nusa Tenggara Timur Province because ithas high economic value and is the best endemic species in the world. The essential oil content in it has a very distinctive aroma and can be used to make various products such as handicrafts, wood carvings, incense, and oils for the perfume and cosmetics industry. Sandalwood is a semi parasitic plant whose life requires a host plant to obtain nutrients and water in the soil. There are many types of host plants that have been used, including casuarina equisetifolia, acacia mangium, sesbania grandiflora, alternanthera sp. and capsicum annum. In this research, sandalwood plants will be tested with the host plant Cymbopogon nardus, which from an economic point of view can provide benefits. Arbuscular Mycorrhizal Fungi (AMF) are a group of fungi from the phylum Glomeromycota which have mutualism symbiosis with higher plant root systems. AMF is able to survive on dry land. The purpose of this study was to analyze the effectiveness of AMF and the use of essential host plants to increase the growth of Sandalwood seeds in Timor Tengah Utara. In the parameter of high increase, the results of the Duncan test showed that the highest AMF treatment for agroforestry land and host chili plants was 19.01, which was different from AMF for agroforestry land within a host plant, Cymbopogon nardus namely 15.44. In the increase in diameter, the results of the Duncan test showed that the AMF treatment of agroforestry land and host chili plants had a significant effect on all treatments, namely 9.11. Duncan test results on plant biomass parameters showed that AMF treatment and host plants chili and lemongrass gave good treatment, namely 3.54 and 3.53 on shoot dry weight parameters and 3.75 and 3.42 root dry weight compared to control, namely 0.27, while at root and shoot ratio seed quality index, the seeds are suitable for use because they comply with the standard. In the parameters of root colonization, AMF and the host plants of chili and lemongrass were both able to adapt well, namely 56.0 and 54.0.